2015
DOI: 10.1007/s10549-015-3287-5
|View full text |Cite
|
Sign up to set email alerts
|

Impact of body mass index on neoadjuvant treatment outcome: a pooled analysis of eight prospective neoadjuvant breast cancer trials

Abstract: Obesity is associated with an increased risk of breast cancer (BC) and poorer outcome. We assessed the impact of body mass index (BMI) on pathological complete response (pCR), disease-free (DFS), and overall survival (OS), according to BC subtypes in patients with primary BC treated with neoadjuvant chemotherapy. 8,872 patients with primary BC from eight neoadjuvant trials were categorized according to BMI: underweight (<18.5 kg/m(2)), normal weight (18.5 to <25 kg/m(2)), overweight (25 to <30 kg/m(2)), obese … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
100
3
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(111 citation statements)
references
References 59 publications
6
100
3
2
Order By: Relevance
“…However, a Chinese report pointed out that high BMI was an independent prognostic factor for TNBC (97). A pooled analysis of eight prospective neoadjuvant breast cancer trials containing >8,800 patients demonstrated that increasing BMI results in decreasing pathological complete response (pCR) rates and that a high BMI exerts detrimental effects on DFS and OS in TNBC (98). Women with ER/PR-negative tumors exhibit a significant association of obesity with clinical outcome, which is also true for ER/PR-positive breast cancer (99).…”
Section: Prognosis Of Tnbcmentioning
confidence: 99%
“…However, a Chinese report pointed out that high BMI was an independent prognostic factor for TNBC (97). A pooled analysis of eight prospective neoadjuvant breast cancer trials containing >8,800 patients demonstrated that increasing BMI results in decreasing pathological complete response (pCR) rates and that a high BMI exerts detrimental effects on DFS and OS in TNBC (98). Women with ER/PR-negative tumors exhibit a significant association of obesity with clinical outcome, which is also true for ER/PR-positive breast cancer (99).…”
Section: Prognosis Of Tnbcmentioning
confidence: 99%
“…7,12,18 The largest of these 12 included a highly selective European trial population with an over-representation of HER2-positive tumors (72%), capped chemotherapy doses at a BSA of 2.0 m 2 and defined HR positivity as ≥10% expression on IHC, all of which make generalization of results challenging. Importantly, in the German analysis, the overweight/obese patients did require significantly more dose reductions in taxanes and in turn in multivariable analysis, dose reductions (but not BMI) negatively affected pCR.…”
Section: Discussionmentioning
confidence: 99%
“…Several series have failed to show a consistent association of BMI with pCR. 712 The largest of these was a pooled analysis of 8 German neoadjuvant trials, which reported a negative association between higher BMI and pCR in their univariate analysis. 12 However, they did not find BMI to predict for pCR in their multivariable analysis which used data from only 2 of the pooled trials.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dawood et al [17] investigated the impact of obesity in 2,311 TNBC patients and were not able to determine any relationship between BMI and survival. However, in a pooled analysis of neoadjuvant trials, it was determined that a higher BMI was associated with lower pathological complete response (pCR), and that there was a detrimental effect on the survival with shorter DFS in obese TNBC patients compared to their non-obese counterparts [19].…”
Section: Discussionmentioning
confidence: 99%